2011
DOI: 10.1158/1078-0432.ccr-09-3069
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Significance of HtrA1 Loss in Endometrial Cancer

Abstract: Purpose: The purpose of this study was to determine if loss of serine protease HtrA1 in endometrial cancer will promote the invasive potential of EC cell lines.Experimental design: Western blot analysis and immunohistochemistry methods were used to determine HtrA1 expression in EC cell lines and primary tumors, respectively. Migration, invasion assays and in vivo xenograft experiment were performed to compare the extent of metastasis between HtrA1 expressing and HtrA1 knocked down clones.Results: Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 17 publications
(33 reference statements)
2
42
0
Order By: Relevance
“…The decrease in expression of these proteins in breast cancer has been previously described as conferring a selective advantage to cancer cells resulting in a more aggressive phenotype. [33][34][35] The reduced expression of fibulin-1 and Sushi domain-containing protein 2 (SUSD2) in bone metastatic cells was consistent with the previously reported role of these proteins in the reduction of cancer cell migration and invasion. 36,37 We were particularly interested in the differential expression of SUSD2 because its gene has been isolated only recently 37 and its expression in breast cancer has never been reported.…”
Section: Differentially Expressed Proteins Involved In Cell Migrationsupporting
confidence: 89%
“…The decrease in expression of these proteins in breast cancer has been previously described as conferring a selective advantage to cancer cells resulting in a more aggressive phenotype. [33][34][35] The reduced expression of fibulin-1 and Sushi domain-containing protein 2 (SUSD2) in bone metastatic cells was consistent with the previously reported role of these proteins in the reduction of cancer cell migration and invasion. 36,37 We were particularly interested in the differential expression of SUSD2 because its gene has been isolated only recently 37 and its expression in breast cancer has never been reported.…”
Section: Differentially Expressed Proteins Involved In Cell Migrationsupporting
confidence: 89%
“…Wang et al reported a significant reduction in HtrA1 expression in breast cancer cell lines compared with their non-tumorigenic counterparts [8]. Downregulation of HtrA1 was also demonstrated by immunohistochemical (IHC) studies in endometrial, esophageal, lung, breast and hepatocellular carcinomas [7,[9][10][11][12][13]. In mesothelioma HtrA1 was suggested as an IHC marker influencing the overall survival [14].…”
Section: Introductionmentioning
confidence: 99%
“…One study has shown that combinatorial treatment of metformin and the chemotherapeutic doxorubicin leads to death of both CSCs and nonstem cancer cells in culture and prolonged relapse rate in a mouse xenograft model of breast cancer cells [23]. Similar promising findings have been seen with other chemotherapeutic agents such as paclitaxel and cisplatin [24,25]. Moreover, CSCs in CRC are CD133 high/CD44 high expressing and exhibit radiation resistance, further investigation is needed to examine the effect of metformin use in patients treated with neoadjuvant or adjuvant chemotherapy on both mortality and relapse rate [26].…”
Section: Discussionmentioning
confidence: 77%